(untitled) (Praxis Educativa, 2025)
The objective of this research was to determine the textual genres used by students in 6 Ecuadorian universities along with their writing purposes, through the application of the European Academic Writing Survey, adapted for Ecuador in 1,732 subjects, teachers (31.4%) and students (68.6%). The results reveal that writing is mainly aimed at demonstrating learning and/or understanding of knowledge instead of developing critical reflection, with a reproductive conception of writing. A greater presence of texts from the Disciplinary Knowledge family (Class Notes, Bibliographic Reviews, Written Exams, Summaries) and to a lesser extent Research and Critical Analysis texts was observed. The least used texts were linked to the Personal Reflection family. A strong polysemy was evident in the naming and description of texts, mainly with the textual genres: Essays, Bibliographic Reviews and Research Reports.